Construction of AIEgens and graphene oxide based aptasensor with two-fluorescent signals for determination of Aflatoxin B1 in food Samples. (December 2022) - Jia, Yongmei; Lai, Qiuxia; Li, Zhiguo; Zhou, Guohua; Liu, Peilian; Lu, Xunbo; Xue, Mingyue; Cheng, Yong
Abstract: Sensitive and accurate determination of aflatoxin B1 in food samples is urgently required for food safety, environment monitoring and human health due to its high toxicity. Here, we constructed an aptasensor with two fluorescent signals for determination of AFB1 in food samples by combining AIEgesns (TPE-Z) as fluorescent probe, the highly specific aptamer molecular label with Cy5 as the recognition element and GO as the fluorescence quencher. Upon the addition of AFB1, the fluorescence signal of the aptasensor platform turn from "off" to "on" with two fluorescent signals. The aptasensor provided a sensitivity (0.04 ng/mL), specificity and reliable approach for AFB1 detection. It had distinct advantage in detection sensitivity compared with single fluorescent signal aptasensor. Moreover, it was applied to analysis AFB1 in food samples (rice, corn and soybean) with satisfactory results. Graphical abstract: Image, graphical abstract